Cenobamate in refractory epilepsy: Overview of treatment options and practical considerations - Bettina Schmitz; Simona Lattanzi; Kristl Vonck; Reetta Kälviäinen; Lina Nashef; Elinor Ben‐Menachem (Epilepsia Open, 2023)
Abstract Management of drug resistant epilepsy (DRE) represents a challenge to the treating clinician. This manuscript addresses DRE and provides an overview of treatment options, medical, surgical, and dietary. It addresses treatment strategies in polytherapy, then focuses on the role cenobamate (CNB) may play in reducing the burden of DRE while providing practical advice for its introduction. CNB is a recently approved, third generation, anti‐seizure medication (ASM), a tetrazole‐derived carbamate, thought to have a dual mechanism of action, through its effect on sodium channels as well as on GABAA receptors at a non‐benzodiazepine site. CNB, having a long half‐life, is an effective add‐on ASM in refractory focal epilepsy with a higher response rate and a higher seizure‐freedom rate than is usually seen in regulatory clinical trials. Experience post‐licensing, though still limited, supports the findings of clinical trials and is encouraging. Its spectrum of action in relation to generalized epilepsies and seizures remains to be established, and there are no data on its efficacy in monotherapy. At the time of writing, CNB has been prescribed for some 50 000 individuals with DRE and focal epilepsy. A larger number is needed to fully establish its safety profile. It should at all times be introduced slowly to minimize the risk of serious allergic drug reactions. It has clinically meaningful interactions which must be anticipated and managed to maximize tolerability and likelihood of successful treatment. Despite the above, it may well prove to be of major benefit in the treatment of many patients with drug resistant epilepsy.